EKOLOGI BAHASA DAN PENGARUHNYA DALAM DINAMIKA KEHIDUPAN BAHASA MELAYU LOLOAN BALI - I Nyoman Suparwa (Bumi Lestari Journal of Environment, 2008)
Ecology of language is interaction between language and its environment. Language can only exist if there are speakers and it is used a means of communication. Language is within the self (mind/soul) of the speakers, it functions as a means of social interaction (communication) also it is concededly created to communicate and it is the result of social life. The dynamics of language interrelated to its environment are affected by the relation between the user/use with the physical/natural, religious and social environment. The formulation of the relation concept applies life philosophy of Balinese society (Hindu) which is generally known as Tri Hita Karana (three causes of bliss) that in linguistic field by the linguists it is only differentiated into natural environment and social environment. This study classified language environment into three kinds according to life philosophy of Balinese and it apparently matched to the phenomenon of the use of Balinese Loloan Malayan language. Natural/physical relation significantly affected in the use of vocabularies related to traditional Loloan Malayan house, house on stilts (Rumah Panggung), such as the word kelam ?wood plank to close the spaces? (placed on windows/doors), sendi ?foundation of house?s pillars?, tontongan ?windows of house on stilts (Rumah Panggung)?, were barely unrecognized except the word sendi which was still found. In religious relation, the vocabularies such as ruah ?celebration?, tungsten ?customary ceremony?, nela?i/kepus pungsed ?the ceremony of loosened umbilical cord in babies?, lepas kambuhan ?the ceremony of forty days after babies? birth? and khitanan ?ceremony of circumcision for boys aged 4-12 years old?, were barely underused except the word khitanan in which the ceremony itself was still prevailed. The last, social relation showed the greatest dynamics because basically language existed depending on its use as a social means (communication). In this matter, there was accommodation of Loloan Malayan language with Balinese and Bahasa Indonesia which was absorbed through the process of adoption, for example the word pait ?pahit? (Balinese) and telepon (Bahasa Indonesia), and process of adaptation, such as the word kuping ?telinga? (Balinese) became koping and the word lain (Bahasa Indonesia) became laen.